Hubungan Faktor Penduduk Usia Produktif, Upah dan Kontribusi Sektor Konstruksi Terhadap Ketimpangan Distribusi Pendapatan di Kabupaten Manokwari - Hidayah, Nur; Orisu, Liliyani M; Rahayu, Yuyun Puji (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2024)
This study aims to identify the relationship between the number of people of productive age, the provincial minimum wage, and the contribution of the construction sector to income inequality in Manokwari Regency. The secondary data used in the study was obtained from the Central Statistics Bureau and related institutions between 2013-2017. Descriptive statistical analysis methods and Pearson correlation explain how the direction of the relationship of each factor. The variables of Productive Population, Minimum Wage, and Contribution of the Construction Sector have a positive and significant relationship with Income Distribution Inequality, both partially and simultaneously. This inequality is caused by the high growth of the productive age population without adequate job availability, the influence of the minimum wage, and investment policies in the construction sector.